The role of emotions in educational processes: the conceptions of teacher educators - Bachler, Rodolfo; Segovia-Lagos, Pablo; Porras, Camila (Frontiers in Psychology, 2023)
The research shows that a very important part of initial teacher education is to reformulate the beliefs that student teachers bring with them from their school experience. These beliefs, which are intuitive in nature, deal with different educational topics and one area that is currently of great importance, due to the emotional turn that the educational system is experiencing, are the beliefs that student teachers hold about the role of emotions in educational processes. In a world full of views that portray emotions as discrete states that are separate from cognitive processes, it is a priority for initial teacher development to train future teachers to hold conceptions that consider the deep emotional-cognitive integration that exists in the human brain. At the same time, this process requires teacher educators (hereafter referred to as TEs) who hold conceptions on this topic that are aligned with the most current scientific knowledge on the subject. However, we do not know how the conceptions that TEs maintain on this topic are, since, until now, research on conceptions has focused on other types of educational topics. Considering the foregoing, this study aimed to evaluate the conceptions that TEs have on this topic, using a questionnaire of dilemmas that was applied to 68 TEs from different universities. The results obtained show that the TEs maintain perspectives on the role of emotions in the teaching and learning processes that oscillate between dualism and emotional-cognitive integration. In addition, it was found that TEs’ perspectives tend to be more integrative when considering attitudinal learning than when considering verbal learning. Finally, the study shows that maintaining integrative perspectives is more difficult when educational situations involve emotions of positive valence that may constitute an obstacle for teaching and learning. The results are discussed, and a series of reflections are elaborated in order to analyze to what extent the beliefs held by TEs are adequate as a cognitive basis for reformulating the conceptions held by student teachers on this issue.